Investigation of Nanostructured and Gas Sensing of Tin Dioxide (Sno2) Films Prepared by Oxidation of Sn - Hasan, Mazin H.; Ibrahim, Fuad T.; Abd, Ahmed Naji (Iraqi Journal of Science, 2019)
Nanostructured tin dioxide (SnO2) thin films were prepared by thermal oxidation of Sn, which were ground and embedded in methanol then it was deposited on a glass substrate utilizing casting method. The deposited films were examined for their morphology, and crystal structure by transmission electron microscopy (TEM) scanning electron microscopy (SEM), and X-ray diffraction (XRD) technique. In most cases, it was found that SnO2 thin films had a tetragonal phase, predominantly grown on preferred (110) and (200) planes. The deposited thin films have grain size was about 82 nm. The sensing properties of SnO2against NO2 gas were studied as a function of working temperature and time under optimal condition. The sensitivity, response time and recovery time were calculated with different operating temperatures.